A ripple suppression strategy based on virtual self-injection APF for quasi-Z source inverter. (October 2018) - Wei, R Y; Tang, Y F; Wang, S J; Li, Z Y
Abstract: The power flows between the DC side and AC side of single-phase quasi-Z source inverter (QZSI) causes double-frequency (2ω) voltage ripple of capacitors, current ripple of inductors. This paper proposes a virtual self-injection active power filter (APF) ripple suppression strategy for the single-phase QZSI without changing the circuit structure, and the 2ω ripple is suppressed by controlling the shoot-through duty cycle based on the thought of ripple vector cancellation. The 2ω ripple model and its generation mechanic for single-phase QZSI are presented through the analysis of the power flows and small signal model for quasi-Z network. Simulation results verify the proposed ripple suppression strategy can effectively reduce the 2ω current ripple of inductors from 18.38% to 3.54%.